The role of electronic word of mouth on halal brand image and purchase intention in halal cosmetics - Zahrah, Wulandini Az; Muslichah, Istyakara; Nazarie, Wan Nur Fazni Wan Mohamad (Asian Journal of Islamic Management (AJIM), 2023)
Purpose – This study aims to determine the effect of altruism, moral obligation, and halal brand image on purchase intention for halal cosmetic products in Indonesia, mediated by e-WOM variables. Methodology – This study uses a purposive sampling method to collect the data. The primary data was collected through questionnaires with criteria of Indonesian Muslims and following halal forum accounts on Instagram, such as @halskin, @halalcorner, @halalcornercommunity, @halalstyleid, and @lppommui.Findings – Altruism positively but not significantly influences e-WOM, moral obligation positively and significantly influences e-WOM, e-WOM positively affects halal brand image and purchase intention, and halal brand image but does not significantly influence purchase intention.Implications – This research is expected to provide directions and suggestions for further studies in the halal industry, especially with regard to the variables in this study. This research is also expected to help marketing managers see the response/reaction of potential customers to the halal brand image they have built so that they can strategize on the responses that already exist in this study. This study also suggests that halal cosmetic product companies can work with halal forums to discuss their products in halal forums. This aims to make people more aware of halal cosmetic products and increase their buying interest in them.Originality/Value – This present study provides empirical studies that show that e-WOM can significantly influence HBI and PI because social media users can respond more positively when other consumers/social media users recommend the products